Nonlinear rotor dynamics of 2D molecular array: topology reconstruction - Lykah, V.A.; Syrkin, E.S. (Вопросы атомной науки и техники, 2012)
Molecular layers with rotational degrees of freedom and quadrupolar interaction between linear molecules are investigated theoretically. We found earlier that alternative orientation of the molecules along and perpendicular to an axis of the rectangular lattice is preferable. Here we find the integral of motion and give the topology analysis of the possible dynamical phases and special points in the long-wave limit. We find the strong anisotropy in the angle space: directions of easy excitation ("valleys'') exist. We show the potential relief reconstruction in dependence on the adsorbed lattice anisotropy.